Twisting of Inflatable Penile Prosthesis Tubing Leading to Device Malfunction and Required Explantation: A Rare Complication - Jordan Sarver; Eriel Emmer; Alex Benben; Matthew Skalak; Daniel Talley; Mazen Abdelhady (Case Reports in Urology)
Erectile dysfunction (ED), the impairment of achieving and maintaining an erection for satisfactory sexual intercourse, is a common pathology that men experience for a variety of different factors. Conservative treatment for ED includes changing medications, lifestyle modifications, and psychotherapy. Pharmaceutical and nonsurgical interventions include phosphodiesterase-5 inhibitors(PDE-5i), intracavernosal medication injections, and vacuum devices. Surgical treatment options for ED have evolved over time and currently include the use of inflatable penile prosthesis (IPP) and malleable penile prosthesis. IPP insertion is usually met with good patient satisfaction. However, complications of device insertion can include corporal perforation, urethral injury, cylinder erosion or extrusion, infection, and mechanical failure, to name a few. Our patient presented with device malfunction and intraoperative assessment showed the IPP tubing twisted at the levels of the reservoir on the first operation and the level of the cylinder and scrotal pump on the second operation. The twisting of the tubing resulted in a nonfunctioning IPP as the fluid was unable to fill the cylinders resulting in an erection. The patient was managed with complete device explanation and reinsertion of a new three-piece IPP per the patient and partner’s request. This is the first case report highlighting this specific complication, and we hope to provide clinicians with the resources to recognize this rare complication.